The Effectiveness of Dental Health Education Programs in Reducing Dental Caries Prevalence among Indonesian Adolescents - Lelyana, Nora; Sarjito, Aris; Sutawidjaya, Ahmad Hidayat (Journal of Ecohumanism, 2024)
Dental caries is a significant public health issue among adolescents in Indonesia, exacerbated by limited access to preventive dental care and oral health education. This study aims to assess the effectiveness of Dental Health Education (DHE) programs in reducing the prevalence of dental caries among Indonesian adolescents. Using a qualitative research approach with secondary data analysis, the study reviews findings from existing literature and reports. The findings indicate that well-implemented DHE programs can reduce dental caries prevalence by 30% to 35%, with significant improvements in oral hygiene behaviors. However, factors such as geographic location, socioeconomic status, and cultural beliefs impact the success or failure of these programs. Rural and low-income communities face additional challenges in accessing dental care and educational resources. Technological innovations, including mobile health platforms, interactive apps, and SMS reminders, have shown promise in enhancing the delivery and effectiveness of DHE programs by making them more accessible and engaging. In conclusion, the success of DHE programs depends on addressing contextual barriers and incorporating technological solutions to improve reach and sustainability.